Propagação de rambutanzeiro (Nephelium lappaceum L.) por enxertia - Barreto, Livia Felicio; Cavallari, Ludmilla De Lima; Venturini, Guilherme Costa [UNESP]; De Andrade, Renata Aparecida [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
There is great genetic diversity of rambutan plants, thus, to establish commercial orchards culture, it is recommended the use of plants vegetatively propagated. Therefore, this research aimed to determine the best method of grafting, graft protection and type of rootstock for its propagation. The experiment was repeated in two seasons (autumn/winter and spring/summer). The experimental design was completely randomized in both experiments, with four replicates, each experimental unit consisted of 10 plants analyzed in a 4x2x2 factorial with four types of grafting (whip graft-WG; cleft graft -CG; wedge graft-WG; and inverted wedge graft-IWG;), 2 types of graft protection (Biodegradable and plastic) and 2 types of rootstock (without or with leaves). The variables analyzed in this study were: percentage of grafting success, number and length of buds (cm). For grafting performed in autumn /winter, both by cleft grafting as whip graft with biodegradable strip and rootstock leafless provided the best results in propagation of rambutan tree. The best results were observed during the autumn / winter.

Devido a grande diversidade genética de plantas de rambutan para estabelecimento de pomares comerciais da cultura recomenda-se o uso de plantas propagadas vegetativamente. Este trabalho teve como objetivo determinar o melhor método de enxertia, proteção do enxerto e tipo de porta enxerto para sua propagação. O experimento foi repetido em duas épocas do ano (outono/inverno e primavera/verão). O delineamento experimental foi inteiramente casualizado em ambos experimentos, com 4 repetições, sendo cada unidade experimental composta de 10 plantas analisadas em um fatorial 4x2x2, sendo 4 tipos de enxertia (inglês simples-IS; fenda cheia-FC; fenda esvaziada-FE; e fenda esvaziada invertida-FEI), 2 tipos de materiais de proteção do enxerto (Biodegradável e Plástico) e 2 tipos de porta enxertos (sem ou com folhas). As variáveis analisadas foram: porcentagem de pegamento; número; e comprimento das brotações (cm). Para as enxertias realizadas no outono/inverno, tanto a garfagem por fenda cheia quanto o inglês simples com fita biodegradável e porta enxerto sem folhas proporcionaram os melhores resultados na propagação do rambutanzeiro. Os melhores resultados foram observados na época outono/inverno.
Propagation of rambutan tree (Nephelium lappaceum L.) for grafting
Keywords: Nephelium lappaceum L.; Grafting; Graft protection; Rootstock; Nephelium lappaceum L; Garfagem; Proteção do enxerto; Porta enxerto